Remotely prescribed, monitored, and tailored home-based gait-and-balance exergaming using augmented reality glasses: a clinical feasibility study in people with Parkinson’s disease - Hardeman, Lotte E. S.; Geerse, Daphne J.; Hoogendoorn, Eva M.; Nonnekes, Jorik; Roerdink, Melvyn (Frontiers in Neurology, 2024)
Background Exergaming has the potential to increase adherence to exercise through play, individually tailored training, and (online) remote monitoring. Reality Digital Therapeutics (Reality DTx®) is a digital therapeutic software platform for augmented reality (AR) glasses that enables a home-based gait-and-balance exergaming intervention specifically designed for people with Parkinson’s disease (pwPD). Objective The primary objective was to evaluate the feasibility and potential efficacy of Reality DTx® AR exergaming intervention for improving gait, balance, and walking-adaptability fall-risk indicators. The secondary objective was to evaluate the potential superiority of AR glasses [Magic Leap 2 (ML2) vs. HoloLens 2 (HL2)]. Methods This waitlist-controlled clinical feasibility study comprised three laboratory visits (baseline; pre-intervention; and post-intervention), a home visit, and a 6-week AR exergaming intervention. Five complementary gait-and-balance exergames were remotely prescribed (default five sessions/week of 30 active minutes/session), monitored, and tailored. Feasibility was assessed in terms of safety, adherence, and user experience. During laboratory visits, gait-and-balance capacity was assessed using standard clinical gait-and-balance tests and advanced walking-adaptability fall-risk assessments. Results In total, 24 pwPD participated. No falls and four near falls were reported. Session adherence was 104%. The User Experience Questionnaire scores for Reality DTx® ranged from above average to excellent, with superior scores for HL2 over ML2 for Perspicuity and Dependability. Intervention effects were observed for the Timed Up and Go test (albeit small), the Five Times Sit to Stand test, and walking speed. Walking-adaptability fall-risk indicators all improved post-intervention. Conclusion Reality DTx® is a safe, adherable, usable, well-accepted, and potentially effective intervention in pwPD. These promising results warrant future randomized controlled trials on the (cost-)effectiveness of home-based AR exergaming interventions for improving gait, balance, and fall risk. Clinical trial registration ClinicalTrials.gov, identifier NCT05605249.